External Finance and Firm Survival in the Aftermath of the Crisis : Evidence from Eastern Europe and Central Asia - Clarke, George R.G. (World Bank, Washington, DC, 2012)
Two data sets are used to study how country and firm characteristics affected firms' financial constraints and their likelihood of survival during the early phase of the recent global financial crisis in Eastern Europe and Central Asia, a region that was especially hard hit. The first data source provides information on the reported severity of financial constraints for 360 firms from 23 countries in 2002, 2005, and 2008. By following the same firms over time, the study summarizes both the gradual easing of financial constraints from 2002 to 2005 and their tightening during the crisis. Key findings are that financial constraints during the crisis were less severe in countries with well-established foreign banks (entered prior to year 2000), and that changes in the severity of financial constraints were more pronounced for large firms than others during the crisis (although large firms continued to have less severe constraints on average). The second data source provides information on whether firms remained in operation in 2009 in six countries in Eastern Europe and Central Asia. Controlling for other relevant characteristics, firms were more likely to survive the crisis if they had access to external credit.